The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.npp.1300002
|View full text |Cite|
|
Sign up to set email alerts
|

Anxious–Retarded Depression: Relation with Plasma Vasopressin and Cortisol

Abstract: Dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis is related to melancholic or endogenous depression; however, the strength of this relationship depends on the definition of the specific depression subcategory. A two-dimensionally defined subcategory, anxious-retarded depression, is related to melancholic depression. Since arginine vasopressin (AVP) activates the HPA axis, and both major depression and the melancholic subcategory are associated with elevated plasma AVP levels, we investigated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 45 publications
3
63
1
6
Order By: Relevance
“…In contrast, AVP mRNA expression in the PVN and SON is unchanged in depressed patients with Alzheimer's disease compared with nondepressed patients with Alzheimer's disease (338). Interestingly, two studies found a correlation between plasma AVP levels and cortisol levels in depression, particularly in suicide victims (112,232), but this finding was contradicted by another report (75). Increased expression of the V1a receptor gene was found in the PVN of depressed patients (529).…”
Section: Anxiety and Depressioncontrasting
confidence: 43%
“…In contrast, AVP mRNA expression in the PVN and SON is unchanged in depressed patients with Alzheimer's disease compared with nondepressed patients with Alzheimer's disease (338). Interestingly, two studies found a correlation between plasma AVP levels and cortisol levels in depression, particularly in suicide victims (112,232), but this finding was contradicted by another report (75). Increased expression of the V1a receptor gene was found in the PVN of depressed patients (529).…”
Section: Anxiety and Depressioncontrasting
confidence: 43%
“…197 Disturbances (hyperactivity) in vasopressinergic activity have also been reported clinically in patients with depression. 198,199 Together, this has led many to hypothesize the utility of central vasopressinergic receptor antagonism as a potentially novel antidepressant strategy.…”
Section: Arginine Vasopressinmentioning
confidence: 99%
“…Several clinical studies suggest that AVP could play an important role in the aetiology of these conditions and elevated plasma levels of AVP have been described in subjects suffering from depression (van Londen et al 1997, 2001, de Winter et al 2003 or post-traumatic stress disorders (de Kloet et al 2007). Post-mortem studies have also shown increased numbers of AVP-expressing neurons in the PVN of depressed patients (Purba et al 1996, Merali et al 2006.…”
Section: Introductionmentioning
confidence: 99%